2018
DOI: 10.1007/s00167-018-5204-z
|View full text |Cite
|
Sign up to set email alerts
|

Femoral tunnel widening is similar between anteromedial portal and transtibial techniques following single-bundle anterior cruciate ligament reconstruction: a systematic review and meta-analysis

Abstract: Purpose In anterior cruciate ligament (ACL) reconstruction, there is concern regarding the potential risk of femoral tunnel widening in the anteromedial portal (AMP) technique due to the acute graft‐bending angle at the aperture and the more elliptical aperture shape of the femoral tunnel compared to the transtibial (TT) techniques. Therefore, the aim of the current systematic review and meta‐analysis was to compare the femoral tunnel widening between the AMP and TT techniques in patients who underwent ACL rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This study included more high-quality RCTs and PCTs and much larger sample sizes than previous meta-analyses and systematic reviews of the same topic. 9,10,36,43,46,47 These factors strongly support the robustness of our conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…This study included more high-quality RCTs and PCTs and much larger sample sizes than previous meta-analyses and systematic reviews of the same topic. 9,10,36,43,46,47 These factors strongly support the robustness of our conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…Computed tomography (CT) was not routinely performed because digital plain radiography has been demonstrated to be a reliable method for detecting bone tunnel enlargement after ACLR 38 and is a widely used modality for evaluation of tunnel widening. 27…”
Section: Evaluation Of Tunnel Widening On Radiographymentioning
confidence: 99%
“…Segawa et al 39 indicated that acute GBA can increase mechanical stress in the femoral tunnel wall, which increases tunnel widening. Other studies 27 , 36 have also confirmed that acute GBA is associated with tunnel widening. Furthermore, acute GBA affects repetitive bending stress on the graft and thus influences graft healing within the joint.…”
mentioning
confidence: 63%